Orthodontic Micro-Implants - Technology And Clinical Applications - Georgeta Zegan (Romanian Society of Oral Rehabilitation, 2009)
The introduction's purpose of orthodontic therapy with micro-implants was to strengthen the skeletal anchorage. Thus, in the specialty literature appeared numerous studies on the evolution of orthodontic micro-implants, technology and diversification of clinical applications. The designs of micro-implants types used in orthodontics are presented, different methods of insertion, the steps of surgical procedures and various areas for placement of orthodontic micro-implants after clinical indications. It is presented an example of a clinical case requiring fixed orthodontic treatment using a micro-implant on the edentulous ridge for solving the problem of orthodontic anchorage.